East European Refugee Symposium - . Centre for Refugee Studies (Refuge, 1990)
On March 29, 1990, the Centre for Refugee Studies organized a symposium at Osgoode Hall Law School, York University, to discuss the Canadian policy towards Eastern Europeans seeking to come to Canada as refugees under the current rapidly-changing circumstances. Participants were invited to express their own opinions based on their knowledge and not to represent any organizational views. Further, it was agreed that there would be no attribution of comments. Nor would the meeting be reported, though the results could be. In any case, there was no commitment by anyone to endorse the results. The intention was to encourage a free exchange of information and ideas without inhibition.